Copper‐Catalyzed Tandem Cyclization Approach to N, O‐Chelated Boron Difluoride Complexes. Issue 4 (27th March 2023) - Cheng, Zemin; Xu, Yue; Zheng, Tao; Yang, Yang; Tang, Feng; Gu, Linghui; Ma, Wenbo
Abstract: A strategy for synthesizing N, O ‐chelated boron difluoride complexes via copper‐catalyzed tandem cyclization of readily available 2‐aryl pyridines has been developed. This reaction tolerates a wide range of functional groups, providing the corresponding products in 43–91% yield. Furthermore, the photophysical properties were investigated by measuring the UV/Vis absorption and fluorescence spectra of several product derivatives. Abstract : An efficient copper ‐catalyzed tandem cyclization of readily available substituted 2‐arylpyridine with Cu(BF4 )2 .6H2 O have been developed to afford N, O ‐chelated boron difluoride complexes in good yields with excellent regioselectivity.